Lychee seed extract improves growth performance and hepatic health in largemouth bass (Micropterus salmoides) fed high-fat diets: Novel insights from network pharmacology and in vivo validation - Zhenye Lin; Qi Li; Wenjie Chu; Shuling Bai; Shan Xie; Xiaotong Chen; Hao Chen; Zhipeng Zheng; Jiandong Zhu; Yongxin Liu; Yingying Yu; Tengfei Zhu (Aquaculture, 2027)

Metallogenesis and exploration vectors of the large-scale Tengjia gold deposit, Jiaodong Peninsula (Eastern China): Constraints from monazite U-Pb geochronology and sulfide geochemistry - Jiayao Hao; Liuan Duan; Yu Zhang; Hongtao Zhao; Yongjun Shao; Yuncheng Guo; Xu Wang; Shuling Song (Journal of Asian Earth Sciences, 2026)

Selective recovery of vanadium, molybdenum, and nickel from full-particle spent hydrodesulfurization catalysts via microwave roasting-ammonia leaching - Haoyu Xu; Liang Yu; Zhiyuan Ma; Shuling Fang; Shuai Rao; Dongxing Wang; Lijuan Duan; Hongyang Cao; Zhiqiang Liu (Journal of Environmental Chemical Engineering, 2026)

Coupling of spectroscopy and nitrogen-oxygen isotopes unveils the mechanisms of dissolved organic matter and nitrate pollution in lakes within the agro-pastoral transition zone - Guodong Chai; Fang Yang; Haiqing Liao; Debin Jia; Weiying Feng; Chiamin Ho; Dongpin Liu; Shuling Chen; Jianguo Liu; Huibin Yu (Journal of Environmental Sciences, 2026)

Designing sustained-release sodium carriers: Oil-modified starch gels enhance the texture and delay sodium release in low-sodium shrimp protein gels - Menghan Wang; Yang Li; Xuening Yu; Rui Liu; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Chemistry, 2026)

Ultrasonically treated pea starch modulates oil absorption in corn starch-based deep-fried products: Insights into gel network architecture, interfacial behavior, and molecular dynamics simulations - Menghan Wang; Xuening Yu; Rui Liu; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Research International, 2026)

Photothermal-photodynamic enhanced antibacterial activity of PDA-ALA nanoparticles enables dual-light-responsive sweet cherry preservation - Jianzhuo Du; Tai Gao; Jialin Wang; Pingyu Ge; Haoyang Du; Yu Tong; Jiapei Wu; Weizhuo Xu; Shuling Zhang; Xu Zhao (Food Bioscience, 2026)

White Spot Syndrome Virus Envelope Protein VP 53 B Functions as a Trypsin Inhibitor and Interacts With Hemocyanin - Wenxu Xia; Lingqi Zhuang; Yuchen Liu; Kai Li; Bing Qin; Shuling Yan; Yongxin Yu; Yongjie Wang (Journal of Fish Diseases, 2026)
White spot syndrome virus (WSSV) remains a persistent and significant threat to the global shrimp aquaculture industry. However, its pathogenic mechanisms remain incompletely understood, and no effective intervention strategies are currently available. In this study, we investigated the functional role of VP53B, an envelope structural protein of WSSV, using a combination of infection bioassays, protein structure prediction, protease inhibition assays and protein binding analyses. Our results demonstrate that VP53B is a critical determinant of per os (oral) infection in shrimp, including Procambarus clarkii (crayfish) and Litopenaeus vannamei (whiteleg shrimp). Functionally, VP53B acts as a trypsin inhibitor and interacts with host hemocyanin. We propose that through modulation of shrimp trypsin and hemocyanin, VP53B disrupts the prophenoloxidase‐activating system, a key innate immune pathway, thereby facilitating successful WSSV infection. This study provides new insights into the molecular mechanisms underlying WSSV oral infectivity and highlights VP53B as a potential target for therapeutic intervention.

Ameliorative effects of dietary curcuminoid supplementation on high-carbohydrate-diet-induced hepatic lipid metabolic disorders in largemouth bass (Micropterus salmoides) - Zhenye Lin; Zhipeng Zheng; Hongmian Mao; Wenjie Chu; Xiaotong Chen; Shan Xie; Shuling Bai; Qi Li; Hao Chen; Yongxin Liu; Jiandong Zhu; Tengfei Zhu; et al. (Aquaculture, 2026)

Data-driven optimization of volatile fatty acid production from food waste in mono- and sludge-integrated co-fermentation systems - Fangnon Firmin Fangninou; Zhengguo Li; Zhan Yu; Guodong Yang; Dan Yu; Shuling Chen (Journal of Environmental Sciences, 2026)

Cracking characteristics of rock-anchored beam system during construction of underground powerhouse under high in-situ stress and complex rock mass structures: A case study of Yebatan hydropower station - Peiyang Yu; Xiuli Ding; Shuling Huang; Xinhao Zhu; Yang Qin; Jianhua He; Yuting Zhang; Gang Han (Tunnelling and Underground Space Technology, 2026)

Apatite geochemistry and Sr isotopes reveal the genesis of Au–W deposits in the Xiangzhong Metallogenic Province, South China: Insights from the Xingfengshan deposit - Lianjie Zhao; Yu Zhang; Han Zheng; Hao Zeng; Hongjie Shen; Shuling Song; Xu Wang (Journal of Asian Earth Sciences, 2026)

Simulating the interactions between per- and polyfluoroalkyl substances and kidney transporters for understanding their half-life and renal bioaccumulation - Yuyan Zhong; Yulu Wang; Yudan Dong; Jinrui Zhang; Yifei Yang; Shuling Yu; Jintao Yuan (Chemico-Biological Interactions, 2026)

Deformation Characteristics of Surrounding Rock in a Large Underground Opening Under High In Situ Stress and Complex Rock Mass Structures: A Case Study of Yebatan Hydropower Station - Peiyang Yu; Xiuli Ding; Shuling Huang; Peng-Zhi Pan; Yuting Zhang; Jianhua He; Ju He; Gang Han (Rock Mechanics and Rock Engineering, 2026)

Hydraulic fracturing-induced gold remobilization: Pyrite geochemical and sulfur isotopic insights from the Liuan lode gold deposit, South China - Xu Wang; Yu Zhang; Zebin Tang; Yongjun Shao; Bing Xiao; Shuling Song; Xingting Sun; Hongtao Zhao; Lianjie Zhao (Journal of Geochemical Exploration, 2026)

Selection of adsorption and immobilization carriers under circulating flow conditions for enhanced performance and metabolic characteristics of Acidithiobacillus ferrooxidans - Fangzheng Zhou; Guanghui Chen; Yanyan Wang; Deshuang Yu; Yifan Zhu; Renjie Lu; Shufang Li; Shuling Xiao; Yingying Dong (Bioresource Technology, 2026)

Chronic Fluoride Exposure from Brick Tea Consumption Disrupts Bone Remodeling and Contributes to Bone Loss in Chinese Population with Skeletal Fluorosis - Hongjiang Long; Yubo Liu; Pinggui Lei; Ting Hu; Zhijuan Shao; Yu Luo; Shuling Zhang; Jinshu Li; Peng Luo; Zhenting Zhang; Shaofeng Wei (Biological Trace Element Research, 2026)

Synergistic curdlan gum/xanthan gum system improves shrimp myofibrillar protein gel properties via enhanced network structure, texture and water holding capacity - Shuling Zhou; Xuening Yu; Menghan Wang; Xiaoyang Liu; Dayong Zhou (Food Research International, 2026)

Optimizing short-wave infrared (SWIR) indications of alteration minerals for deep mineralization exploration in the Qianchuiliu lode gold deposit, Jiaodong Peninsula - Hongtao Zhao; Liuan Duan; Yu Zhang; Xiaomeng Han; Yongjun Shao; Yuanming Pan; Yuzhou Feng; Xu Wang; Shuling Song; Hongjie Shen (Journal of Geochemical Exploration, 2026)

Multiplex PCR and nanopore sequencing reveal the genetic stability of Hantaan virus in Xi’an, China - Hailong Chen; Peng Zhang; Xiaoyue Chu; Yangni Deng; Mengying Yu; Leile Zhang; Quanli Du; Yuewen Han; Yujie Yang; Zerun Xue; Shuling Li; Rui Wu; et al. (Archives of Virology, 2026)

Mechanisms of blue light-mediated inhibition of chlorophyll degradation in ‘Newhall’ sweet orange during postharvest - Hui Sun; Yuwei Zhou; Sijia Liu; Qianqian Yu; Mengyao Yin; Chen Huan; Xiaolin Zheng; Shuling Shen (Postharvest Biology and Technology, 2026)

Mechanisms of water-rock interaction and its impact on swelling and crack behavior of argillaceous dolomite in tunnel uplift zones - Zihang Liu; Kang Huang; Shuling Huang; Xianfeng Liu; Fei Yu; Shanxiong Chen; Zhangjun Dai (Bulletin of Engineering Geology and the Environment, 2026)

Effect of the downward bevel angle on the particle radial migration behaviour and secondary flow in spiral separators - Meng Lingguo; Gao Shuling; Liu Tianlin; Kuang Jingzhong; Yu Mingming (Minerals Engineering, 2025)

High-strength crosslinked MXene/CNT/PEEK composites for electromagnetic interference shielding and infrared camouflage in extreme environments - Yu Bai; Chunqi Guo; Liubo Liang; Shengdao Wang; Xiaohan Mei; Yanxu Lu; Jianpeng Jiao; Guibin Wang; Shuling Zhang (Chemical Engineering Journal, 2025)

Polyetheretherketone-based foam with low reflectivity and high electromagnetic interference shielding effectiveness suitable for harsh service environments - Liubo Liang; Tonghua Wu; Xiaohan Mei; Yu Bai; Chunqi Guo; Yanchao Yang; Guibin Wang; Shuling Zhang; Jianxin Mu (Chemical Engineering Journal, 2025)

Molecular interactions and physiological effects of oyster-derived synthetic peptide-calcium complex: Insight in improving the bone growth and health - Xuening Yu; Guang Li; Shijie Dou; Shuling Zhou; Xiaoyang Liu; Dayong Zhou (Food Research International, 2025)

Corrigendum to “Piezophotocatalysis of ZnO@PVDF coaxial nanofibers modified with BiVO4 and Ag for the simultaneous generation of H2O2 and removal of pefloxacin and Cr(VI) in water” [Chem. Eng. J. 484 (2024) 149514] - He Lv; Yanan Liu; Jianfeng Zhou; Yubin Bai; Hongpu Shi; Bin Yue; Shuling Shen; Deng-Guang Yu (Chemical Engineering Journal, 2025)

Decoupling of Au and W mineralization in the Xiangzhong Metallogenic Province (South China): Insights from the Xingfengshan Au–W deposit - Lianjie Zhao; Yu Zhang; Kofi Adomako-Ansah; Matthew J. Brzozowski; Hao Zeng; Chenghua Shi; Yongjun Shao; Hongtao Zhao; Hongjie Shen; Xu Wang; Shuling Song; Xiyue Zheng (Gondwana Research, 2025)

Impacts of shale gas wastewater leaks on neighboring crops: Physiological and morphological responses of tomatoes - Fengming Li; Xulin Yu; Yushun Yang; Wei Tao; Mengting Zhu; Di Zhang; Shuling Shi; Huiqiang Li; Peng Tang; Alberto Tiraferri; Baicang Liu (Process Safety and Environmental Protection, 2025)

Influence of ionic concentration in sludge on its deep dewatering behavior and electro-kinetic process - Xiaoyan Yu; Yingte Li; Sumeng Du; Saisai Su; Shuling Zhang (Journal of Water Process Engineering, 2025)

Overexpression of OsGASR1 promotes Al tolerance in rice - Shuling Cao; Liyun Peng; Jinyu Yu; Ziheng Li; Zhigang Wang; Dan Ma; Xiaoqian Sun; Huawei Zheng; Baolei Zhang; Xingxiang Chen; Zhufeng Chen; Jixing Xia (Plant Science, 2025)

Moisture-absorbing expansion and cracking characteristics of central Sichuan red-bed mudstone based on digital speckle correlation method - Kang Huang; Zhangjun Dai; Shuling Huang; Fei Yu; Shichang Li; Kaiwen Tong; Wei Zhang; Shanxiong Chen (Bulletin of Engineering Geology and the Environment, 2025)

Spatio-temporal variations and influencing factors analysis of coastal wetlands in Tianjin, China - Shuling Yu; Maihemutijiang Mijiti; Min Song; Jingxuan Xu; Dongfang Yuan; Wei Xu (Regional Studies in Marine Science, 2024)

A New Sphalerite Thermometer Based on Machine Learning with Trace Element Geochemistry - Hongtao Zhao; Yu Zhang; Yongjun Shao; Jia Liao; Shuling Song; Genshen Cao; Ruichang Tan (Natural Resources Research, 2024)

Effects of Taurine and Enzymatic Cottonseed Protein Concentrate Supplementation in Low-Fishmeal Diet on Growth, Liver Antioxidant Capacity, and Intestinal Health of Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Zhong Huang; Jun Wang; Yun Wang; Wei Yu; Heizhao Lin; Zhenhua Ma; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2024)
This study was conducted to investigate the impacts of the dietary addition of taurine and enzymatic cottonseed protein concentrate (ECPC) in low-fishmeal diet on the growth performance, plasma biochemical indices, hepatic antioxidant capacity, intestinal anti-inflammatory capacity, intestinal microflora, and muscle quality of golden pompano (Trachinotus ovatus). A total of three isonitrogenous diets were given to 225 golden pompanos (5.6 ± 0.14 g). They were randomly divided into nine cages (1.0 m × 1.0 m × 1.5 m; three cages per treatment) with equal stocking numbers of twenty-five fish per cage. The results indicated that the CSM-TC group significantly increased the growth performance of juvenile T. ovatus (p

Effective and mechanistic insights into shale gas wastewater reverse osmosis concentrate treatment using ozonation-biological activated carbon process - Mengting Zhu; Peng Tang; Xulin Yu; Fengming Li; Shuling Shi; Di Zhang; Jialin Shi; Wei Tao; Xia Ruan; Lujian Liu; Baicang Liu (Science of The Total Environment, 2024)

Multigenerational effects of disperse blue 79 at environmentally relevant concentrations on zebrafish (Danio rerio) fecundity: An integrated approach - Chao Wang; Wen Gu; Shaoping Zhang; Li Li; Jian Kong; Hong Zhi; Juan Liu; Mengmeng Wang; Ke Miao; Qi Li; Jie Yu; Runming Wang; et al. (Journal of Hazardous Materials, 2024)

The virulence plasmid associated with AHPND in shrimp appears to have originated from Vibrio owensii through a process of homologous recombination of parental plasmids and the transposable insertion of two large fragments - Yesheng Yan; Haojie Lu; Xiaosha Liang; Tianqi Xu; Shuling Yan; Yongxin Yu; Yongjie Wang (Journal of Invertebrate Pathology, 2024)

The application of multi-point FBG bolt in measuring the excavation damaged zone of underground caverns - Gang Han; Shuling Huang; Xiuli Ding; Yuting Zhang; Jun He; Pengcheng Liu; Peiyang Yu; Dengxue Liu (Tunnelling and Underground Space Technology, 2024)

Self-sacrificed construction of versatile nanoadjuvant for synergistically enhanced immunogenic cell death and improved anti-tumor immunity - Peng Hu; Xiaowen Peng; Shuang Zhao; Fan Li; Guoye Yang; Wujie Guo; Shuling Yu; Jianjun Cheng; Juan Cen; Jiahua Shi (Chemical Engineering Journal, 2024)

A Three-dimensional Anisotropic Creep Model for Predicting the Time-dependent Deformation of Layered Rock Mass - Shuling Huang; Jinxin Zhang; Xiuli Ding; Gang Han; Peiyang Yu; Xuanting Fan (Rock Mechanics and Rock Engineering, 2024)

Efficient piezophotocatalysis of ZnO@PVDF coaxial nanofibers modified with BiVO4 and Ag for the simultaneous generation of H2O2 and removal of pefloxacin and Cr(VI) in water - He Lv; Yanan Liu; Jianfeng Zhou; Yubin Bai; Hongpu Shi; Bin Yue; Shuling Shen; Deng-Guang Yu (Chemical Engineering Journal, 2024)

Evolution of a tidal channel network in the Yellow River Delta, China, and simulation of optimization scenarios - Chengjie Xie; Baoshan Cui; Tian Xie; Shuling Yu; Zhonghua Ning (Journal of Environmental Management, 2024)

HNF4A as a potential target of PFOA and PFOS leading to hepatic steatosis: Integrated molecular docking, molecular dynamic and transcriptomic analyses - Rui Li; Zijing Zhang; Yuxin Xuan; Yulu Wang; Yuyan Zhong; Lingyin Zhang; Jinrui Zhang; Qian Chen; Shuling Yu; Jintao Yuan (Chemico-Biological Interactions, 2024)

Influence of extractable organic components on shale wettability: Dongyuemiao member of Jurassic Ziliujing formation in the Fuxing area, Eastern Sichuan Basin - Weihang Zhang; Rui Yang; Zhiliang He; Hanyong Bao; Hui Yu; Shuling Xiong; Yuanjia Han; Qinhong Hu; Sheng He (Marine and Petroleum Geology, 2023)

Effects of Fermented Cottonseed Meal Substitution for Fish Meal on Intestinal Enzymatic Activity, Inflammatory and Physical-Barrier-Related Gene Expression, and Intestinal Microflora of Juvenile Golden Pompano (Trachinotus ovatus) - Zhanzhan Wang; Shuling Liao; Jun Wang; Yun Wang; Zhong Huang; Wei Yu; Xiaolin Huang; Heizhao Lin; Maoyan Luo; Zhenyan Cheng; Chuanpeng Zhou (Fishes, 2023)
The present study was conducted to investigate the effects of dietary fermented cottonseed meal (FCSM) substitution for fish meal on intestinal enzymatic activity, inflammatory and physical-barrier-related gene expression, and intestinal microflora of juvenile golden pompano. The 375 golden pompanos were divided into 15 groups of 25 fish each, with three replicates for each experimental group. The fish were fed five experimental diets (0 (FM), 12.5% (CSM12.5), 25% (CSM25), 50% (CSM50), and 100% (CSM100) substitution levels) for 8 weeks. The fish were reared and fed the experimental diets under a natural-day light cycle. Compared with the control group, the activities of AMY (amylase) enzymes in the CSM12.5 group and all other groups were elevated (p

Experimental investigation of thermodynamic and kinetic behaviors from water vapor adsorption on four typical clay minerals - Shuling Xiong; Manfei Chen; Hui Yu; Weihang Zhang; Qinhong Hu; Sheng He; Rui Yang (Gas Science and Engineering, 2023)

Slope position mediates the co-utilization of phosphorus by plants and microbes through rhizosphere processes in a phosphorus-limited forest - Tianyi Qiu; Jialuo Yu; Liyuan He; Ji Liu; Qingliang Cui; Yongxing Cui; Chengjiao Duan; Shuling Zhao; Yunqiang Wang; Linchuan Fang (CATENA, 2023)

Prediction of the Endocrine disruption profile of fluorinated biphenyls and analogues: An in silico study - Yuyan Zhong; Jing Ren; Rui Li; Yuxin Xuan; Wu Yao; Qianye Yang; Yin Gan; Shuling Yu; Jintao Yuan (Chemosphere, 2023)

Correction to: Spatial pattern of the effects of human activities on the land surface of China and their spatial relationship with the natural environment - Shuling Hu; Bin Yu; Shen Luo; Rongrong Zhuo (Environment, Development and Sustainability, 2022)

Deletions in GSN gene associated with growth traits of four Chinese cattle breeds - Ao Qi; Wenxiu Ru; Yangkai Liu; Yu Yang; Jia Tang; Haiyan Yang; Shuling Yang; Kaixing Qu; Xianyong Lan; Chuzhao Lei; Bizhi Huang; Hong Chen (Molecular Genetics and Genomics, 2022)

Different toxicity to liver and gill of zebrafish by selenium nanoparticles derived from bio/chemical methods - Shuling Fan; Ying Yang; Lu Sun; Bin Yu; Chunxiao Dai; Yuanyuan Qu (Environmental Science and Pollution Research, 2022)

Spatial pattern of the effects of human activities on the land surface of China and their spatial relationship with the natural environment - Shuling Hu; Bin Yu; Shen Luo; Rongrong Zhuo (Environment, Development and Sustainability, 2022)

Longitudinal Dynamics of Hydrological Connectivity in the Yellow River Delta, China - Chengjie Xie; Baoshan Cui; Zhonghua Ning; Shuling Yu; Tian Xie (Frontiers in Marine Science, 2022)
River deltas are formed by the interaction of connecting water and sediment, and they are among the most economically and ecologically valuable ecosystems on Earth. Because of their special locations, together with direct and indirect human interference, river deltas are expected to be more vulnerable and fragmented. The increasing fragmentation of deltas is largely due to longitudinal hydrological connectivity disruption caused by human activities. However, the dynamics of longitudinal connectivity are unknown, especially in the Yellow River Delta (YRD), which has been subjected to heavy reclamation in recent years. In this study, we divided the whole YRD into three subregions, the erosion zone, the oilfield zone and the deposition zone, and then we used indicators to explore the spatiotemporal variation in hydrological connectivity on the whole scale and on the zonal scale of the delta during 1984-2018 in the YRD. We found that the variation in longitudinal hydrological connectivity was closely related to the geometry of the tidal channel networks, and that the changes in longitudinal hydrological connectivity varied with research scales. A weak increasing trend of connectivity was found on the whole scale of the delta during the past three decades. A decreasing trend of connectivity was found in both the erosion zone and the oilfield zone. In the deposition zone, however, the connectivity degree was enhanced. Furthermore, we also identified the key impaired area and relatively stable area of hydrological connectivity in the YRD and implied that the key impaired area may be a priority restoration zone of the impaired hydrological connectivity zone. Our study provides useful scientific guidance for the subsequent restoration of damaged wetlands.

Bibliometric Review of Biodiversity Offsetting During 1992–2019 - Shuling Yu; Baoshan Cui; Chengjie Xie; Ying Man; Jing Fu (Chinese Geographical Science, 2022)

Characterization of Water Quality in Xiao Xingkai Lake: Implications for Trophic Status and Management - Shuling Yu; Xiaoyu Li; Bolong Wen; Guoshuang Chen; Anne Hartleyc; Ming Jiang; Xiujun Li (Chinese Geographical Science, 2021)

Petrogenesis and tectonic setting of Late Devonian I-type granitic plutons in the Kekesala area, Chinese western Tianshan: implication for tectonic evolution of the North Tianshan Ocean - Zuopeng Wang; Yongjun Li; Gaoxue Yang; Le Wu; Yu Wan; Philemon Lindagato; Shuling Li (International Geology Review, 2021)

Brominated and phosphate flame retardants from interior and surface dust of personal computers: insights into sources for human dermal exposure - Lehuan Yu; Shuling Ru; Xiaobo Zheng; Shejun Chen; Huiying Guo; Guijuan Gao; Yuan Zeng; Yijie Tang; Bixian Mai (Environmental Science and Pollution Research, 2021)

Ecological Offsetting in China’s Coastal Wetlands: Existing Challenges and Strategies for Future Improvement - Shuling Yu; Baoshan Cui; Chengjie Xie; Xu Ma; Ying Man; Zhonghua Ning (Chinese Geographical Science, 2019)

Cloning, sequencing and characterization of the genome of a recombinant norovirus of the rare genotype GII.P7/GII.6 in China - Hui Cai; Yongxin Yu; Miao Jin; Yingjie Pan; Shuling Yan; Yongjie Wang (Archives of Virology, 2017)

Rapid detection of infectious hypodermal and hematopoietic necrosis virus (IHHNV) by real-time, isothermal recombinase polymerase amplification assay - Xiaoming Xia; Yongxin Yu; Linghao Hu; Manfred Weidmann; Yingjie Pan; Shuling Yan; Yongjie Wang (Archives of Virology, 2015)

Genome-wide methylation changes are associated with muscle fiber density and drip loss in male three-yellow chickens - Yonghong Zhang; Jiang Guo; Yan Gao; Shuling Niu; Chun Yang; Chunyan Bai; Xianzhong Yu; Zhihui Zhao (Molecular Biology Reports, 2014)

Cellular Expression of INK4a Gene in Cells of Bladder Cancer Associated with Human Papilloma Virus-16 - G. M. Volgareva; L. E. Zavalishina; D. A. Golovina; Yu. Yu. Andreeva; V. D. Ermilova; O. B. Trofimova; D. A. Kuevda; O. Yu. Shipulina; V. A. Glazunova; Shuling Cheng; L. S. Pavlova; N. L. Cheban; et al. (Bulletin of Experimental Biology and Medicine, 2010)